Pyoderma gangrenosum: A single-center case series study of 32 cases - Güngör, Malik; Yaşar Subaşı, Gülbin; Bilgiç, Aslı; Akman, Ayşe; Yılmaz, Ertan; Alpsoy, Erkan (Trends in Immunotherapy, 2023)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis with multiple different clinical presentations and associated comorbidities. It often presents as ulcerated lesions with a violet/erythematous border and an irregular undercut margin. In this largest single-centre case series study in Antalya-Turkey, we reviewed 32 PG patients diagnosed consecutively within the last 5-year period. Consistent with the literature, PG morphologically often presented with the ulcerative clinic (90.6%), and inflammatory bowel disease (15.6%) was the most common etiologic factor. In our study, female gender predominance (78.2%), lower extremity localization (93.7%), and the rate of multiple ulcers at diagnosis (90.6%) were more prominent than in the literature. Unlike the literature, oral mucosa involvement and syndromic form (both, 6.2%) of the disease were detected more frequently. Our results indicate that PG patients may show differences according to geographical and ethnic differences and/or characteristics of the healthcare institution.